ANALISIS PARTISIPASI MASYARAKAT DALAM PROGRAM KESERASIAN SOSIAL BERBASIS MASYARAKAT DI DESA LORU KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Muhdar, Muhdar (Katalogis, 2015)
This study aims to determine the forms of community participation, community participation levels and to determine the factors that influence people's participation in the program for community-based social harmony in Loru village, Sigi Biromaru Sub-district, Sigi Regency. The number of population in this study was 464 households and the sample is determined by probability sampling with simple random sampling technique. The number of samples are identified by using the formula of Taro Yamane with the smallest level of precision used was 10% so thatthe number of samples are 82 people. The results of descriptive statistical analysis shows that the forms of public participation in the Program for Community-Based Social Harmony in Rural Loruare various, such as, there were donating money, energy, giving an idea or proposal and contribute materials, even those communities participate by giving more than one of participation. The level or degree of community participation is measured by adding the scores.The results show that the level of public participation in the Program for community-based social harmony in Loru village include in partnership level, which at this level of society will have the division of responsibilities in planning, decision control, policy and solving various problems. Partnership includes the degree of citizen power, or the degree to which the public has had power. Furthermore, the result of logistic regression statistical analysis shows that the factor of gender, age, education level, income level, livelihood, accommodating, public awareness and motivation has a probability of affecting people's participation in the program for community-based social harmony in Loru village, Sigi Biromaru district-Sigi Regency.